Determinan Akuntabilitas Pengelolaan Dana Desa - Anandita Zulia Putri; Helda Endardika; Ningrum Pramudiati; Lulu Amalia nusron (Universitas PGRI Yogyakarta, 2022)
This research is useful in assessing the influence of human resource competence, community participation, government internal control system, and accessibility of financial reports have an impact on village fund management accountability. The research uses quantitive data. The population in this research is 7 sub-districts in the Kulon Progo regency with 50 villages. The sample of this research is 168 respondents using the purposive sampling technique. The analytical method used is multiple linear regression with SPSS version 26. This research reveals that human resource competence, community participation, government internal control system, and accessibility of financial reports positively impact village fund management accountability